2022
DOI: 10.1186/s40001-022-00881-y
|View full text |Cite
|
Sign up to set email alerts
|

The association between the body height and cardiovascular diseases: a retrospective analysis of 657,310 outpatients in Germany

Abstract: Background Cardiovascular disease (CVD) represents the leading cause of death worldwide. The identification of individuals at increased risk of CVD is essential to reduce its morbidity and mortality globally. Based on existing data on a potential association between the individual body height and the risk for CVD, we investigated this association in a large cohort of outpatients in Germany. Methods A total of 657,310 adult outpatients with availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It is necessary to investigate the risk factors of CAD for prevention and treatment. Observational studies have identified that adiposity, height, and lipoprotein metabolism are associated with the risk of CAD (Emerging Risk Factors Collaboration, 2011;Krieg et al, 2022;Rader and Daugherty, 2008). To further disentangle the causal relationship between those potential risk factors and CAD, we applied MVMR-PRESS and other existing MR methods to their GWAS summary statistics.…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…It is necessary to investigate the risk factors of CAD for prevention and treatment. Observational studies have identified that adiposity, height, and lipoprotein metabolism are associated with the risk of CAD (Emerging Risk Factors Collaboration, 2011;Krieg et al, 2022;Rader and Daugherty, 2008). To further disentangle the causal relationship between those potential risk factors and CAD, we applied MVMR-PRESS and other existing MR methods to their GWAS summary statistics.…”
Section: Coronary Artery Diseasementioning
confidence: 99%